Analysis of the Development of Religious Tourism At The Maqam Keramat Nangtung - Rohendi, Nanda Talia; Aulia Putri Effendi, Aulia Putri; Avrilianti, Wina; Setiawan, Jaka; Rivas, Prietho (SINTESA, 2024)
This study aims to analyze the development of religious tourism at Maqam Keramat Nangtung, which is an important site in the context of the spiritual and cultural aspects of the local community. The research method used is qualitative, with data collection techniques through observation, interviews, and documentation. The results of the study indicate that the development of tourism that can be undertaken to attract visitor interest includes improving facilities and infrastructure with government support, as well as providing understanding and education to the community regarding the utilization of the tourism area. This is expected to encourage the community to actively participate, such as selling food or goods around the tourist site. Additionally, the use of social media as a promotional tool is expected to reach a wider audience and increase the visibility of Maqam Keramat Nangtung as a religious tourism destination. This study is expected to provide recommendations for managers and stakeholders in formulating sustainable development strategies for religious tourism in this area